First Neuromuscular Contact Correlates with Onset of Primary Myogenesis in Rat and Mouse Limb Muscles - Hurren, Bradley; Collins, Jennifer J. P.; Duxson, Marilyn J.; Deries, Marianne (PLOS ONE, 2015)
Skeletal muscle development has been the focus of intensive study for many decades. Recent advances in genetic manipulation of the mouse have increased our understanding of the cell signalling involved in the development of muscle progenitors which give rise to adult skeletal muscles and their stem cell populations. However, the influence of a vital tissue type – the peripheral nerve—has largely been ignored since its earliest descriptions. Here we carefully describe the timing in which myogenic progenitors expressing Pax3 and Pax7 (the earliest markers of myogenic cells) enter the limb buds of rat and mouse embryos, as well as the spatiotemporal relationship between these progenitors and the ingrowing peripheral nerve. We show that progenitors expressing Pax3 enter the limb bud one full day ahead of the first neurites and that Pax7-expressing progenitors (associated with secondary myogenesis in the limb) are first seen in the limb bud at the time of nerve entry and in close proximity to the nerve. The initial entry of the nerve also coincides with the first expression of myosin heavy chain showing that the first contact between nerves and myogenic cells correlates with the onset of myogenic differentiation. Furthermore, as the nerve grows into the limb, Pax3 expression is progressively replaced by Pax7 expression in myogenic progenitors. These findings indicate that the ingrowing nerve enters the limb presumptive muscle masses earlier than what was generally described and raises the possibility that nerve may influence the differentiation of muscle progenitors in rodent limbs.